International Cross-Listing and Visibility - Baker, H. Kent; Nofsinger, John R.; Weaver, Daniel G. (Journal of Financial and Quantitative Analysis, 2002)
This study shows that international firms listing their shares on the New York Stock Exchange (NYSE) or the London Stock Exchange (LSE) experience a significant increase in visibility, as proxied by analyst coverage and print media attention (The Wall Street Journal or Financial Times). The increase in analyst following is also associated with a decrease in the cost of equity capital after the listing event in a way consistent with Merton's (1987) investor recognition hypothesis. Our results are stronger for NYSE listing firms than for LSE listing firms. This may partially compensate firms for the higher costs associated with NYSE listing (compared to LSE listing).